A stochastic programming model of salinity in the Colorado River Basin - Lee, Donna J., author; Howitt, Richard E., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1989)
Along the Colorado River, naturally occurring salts underlie basin soils. Irrigation water leaches salt from the soil and return flows transport the salt to the river. As a result of salinity, downstream agricultural, municipal, and industrial uses suffer millions of dollars in damages each year. Weather variability can induce large swings in river flow volume, and hence river salinity. During periods of drought, problems due to salinity are worst. Currently, water quality policy decisions are based on average river flows. As a result, river water quality may exceed federal salinity standards during low flow years. This research details an approach for selecting mitigation alternatives to meet or exceed water quality standards under variable river flow conditions. Decisions are based on the value of clean water to downstream agriculture, the cost of mitigation, the variability of river flows, and the risk criteria of policy makers. Regions included in the model are the Grand Valley and Lower Gunnison Basin in Colorado, the Uinta Basin and the Price and San Rafael Regions in Utah, and the Imperial Valley in California.
USCID regional meetings -- 1989
Salinity in the Colorado River Basin
Not digitized by CSUL Digital Services.
Presented at Planning for water shortages: water reallocations and transfers drought management: proceedings from the 1989 regional meetings held on August 24-25, 1989 in Boise, Idaho and on October 19-21, 1989 in St. Louis, Missouri.